The Casa de España: a failed institutional project of Falangism in Buenos Aires (1940-1942) (Quinto Sol, 2020)
This paper studies the constitution of Casa de España (House of Spain), an entity that operated in the city of Buenos Aires between 1940 and 1942 with the purpose of providing a new institutional framework to the Falange Española Tradicionalista and the Juntas de Ofensiva Nacional Sindicalista in Argentina and bringing together different supporters of Francoist regime existing in the city after the end of the Civil War in Spain. Resistance and oppositions generated by this associative project imposed from Spain are analyzed in the nucleus of the Spanish immigration community of Buenos Aires.
Keywords: Spanish Civil War; Francoism; Spanish immigration